2016
DOI: 10.1177/0192513x14561519
|View full text |Cite
|
Sign up to set email alerts
|

Mexican Immigrant Wives’ Acculturative Stress and Spouses’ Marital Quality

Abstract: With a sample of 120 Mexican-origin couples, we examined the extent to which wives' marriage work (i.e., discussions about marital concerns) with husband and marriage work with friend moderated associations between wives' acculturative stress and spouses' marital satisfaction and marital negativity. Results from a series of multiple regression analyses showed that wives' marriage work with husbands (a) served to protect husbands' marital quality from wives' acculturative stress and (b) was linked with greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Considering that close relationships and familial support are facets of resilience, adherence to this value may lead couples to place greater value on family cohesion during a time of increased stress and uncertainty. Preliminary research in support of this has found that, among heterosexual Latine couples, wives may be more likely to engage in open communication with their husbands about relationship concerns compared to non-Latine Whites, and that this behavior is directly associated with wives’ and husbands’ reports of greater marital satisfaction (Rodriguez et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Considering that close relationships and familial support are facets of resilience, adherence to this value may lead couples to place greater value on family cohesion during a time of increased stress and uncertainty. Preliminary research in support of this has found that, among heterosexual Latine couples, wives may be more likely to engage in open communication with their husbands about relationship concerns compared to non-Latine Whites, and that this behavior is directly associated with wives’ and husbands’ reports of greater marital satisfaction (Rodriguez et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, cultural adaptation processes appear to influence associations between mental health outcomes, relationship behaviors, and relationship outcomes. Specifically, Rodriguez et al (2016) found that high levels of marriage work behaviors (defined as reliance on spouses and close friends to support a healthy marriage) protected against the adverse influence of greater wife acculturative stress on husband marital satisfaction. Moreover, at high levels of marriage work, greater wife acculturative stress was significantly associated with lower husband marital negativity.…”
Section: Marriage and Relationship Functioning Among Us Latinesmentioning
confidence: 99%
“…As the social network can either support or undermine romantic relationships (Milardo, 1982), it is important to tap into both positive and negative romantic functioning outcomes (Horwitz, McLaughlin, & White, 1998). Consistent with the extant literature (Helms et al, 2003;Rodriguez et al, 2014), we examined both love and conflict to capture change in both positive and negative aspects of the relationship.…”
Section: Current Studymentioning
confidence: 96%
“…Despite repeated calls in the literature (Huston, 2000;Milardo, 1982), few researchers have considered the role of the social network in shaping romantic dynamics. Those studies that have examined the impact of disclosing romantic problems to partners and friends have focused on middle-aged couples with children (e.g., Helms, Crouter, & McHale, 2003;Proulx, Helms, & Payne, 2004;Rodriguez, Helms, Supple, & Hengstebeck, 2014). Given that young adulthood represents a time of considerable romantic instability, researchers should now not only turn their attention to understanding disclosure processes at this critical life stage but also track disclosure patterns to partners and friends over time and their potential links to romantic outcomes.…”
Section: Current Studymentioning
confidence: 99%
“…Indeed, perspective taking has been found to increase relationship satisfaction (M. Davis & Oathout, 1987), perhaps because it predicts less conflict and more supportive behaviors (Corcoran & Mallinckrodt, 2000;Shih, Wang, Trahan Bucher, & Stotzer, 2009). Given each of these factors, and to answer the call for observational studies of RW (Julien et al, 2000;Rodriguez, Helms, Supple, & Hengstebeck, 2016), in the current study, we set out to examine the following research questions:…”
Section: Rw and Physiologymentioning
confidence: 99%